Pelaksanaan Promosi Tiktok Ditoko Online Devaira - Nabila Salsa Azzahra; Rudi Kurniawan (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
The development of digital technology has revolutionized how small and medium enterprises (SMEs) implement marketing strategies, particularly through social media platforms such as TikTok. This study aims to analyze the TikTok-based content promotion strategy carried out by Toko Devaira, a local fashion brand that has successfully built brand awareness and increased sales through a creative and structured approach. Using a qualitative descriptive method, this research explores the creative process behind promotional content creation, from concept development and production to content distribution using TikTok features such as try-on hauls, dance challenges, and live streaming. The findings indicate that Toko Devaira's promotional strategy reflects the application of Integrated Marketing Communication (IMC) and the AIDA model, successfully generating high engagement through direct interaction with the audience. This study provides practical insights for MSME players in developing relevant, effective, and consumer-experience-based digital marketing strategies.